Assessment of noise from equipment and processes at construction sites. Issue 1 (March 2017) - Lee, Heow Pueh; Wang, Zhaomeng; Lim, Kian Meng
Noise pollution from construction sites has become a major problem for major cities with the continued rapid development as well as redevelopment of cities. These construction sites, in particular for new subway systems, are often near to residential and commercial buildings. A better understanding and characterization of noise profiles will be required for project management and planning as well as environmental impact assessment. In this study, instead of using the typical type 1 sound level meters for the measurement of noise profiles emitted from construction equipment and processes commonly done in construction industry, we attempt to characterize the noise profiles of common construction equipment at their respective noise source using an Acoustic Array or Acoustic Camera. The study also highlighted the significant presence of low-frequency noise at construction sites for some construction equipment and processes. This may have some implications for the design of noise barriers at construction sites.